2022
DOI: 10.3389/fmicb.2022.854131
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Probiotic Properties of a Strain of Lactobacillus plantarum for Shrimp Farming: From Beneficial Functions to Safety Assessment

Abstract: In recent years the safety of probiotics has received increasing attention due to the possible transfer and spread of virulence factors (VFs) and antibiotic resistance genes (ARGs) among microorganisms. The safety of a strain of Lactobacillus plantarum named W2 was evaluated in phenotype and genotype in the present study. Its probiotic properties were also evaluated both in vivo and in vitro, including adherence properties, antibacterial properties and beneficial effects on the growth and immunity of Pacific w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 90 publications
2
6
0
Order By: Relevance
“…In present study examining LAB strains for hemolytic activity, 16 strains were found to be non-hemolytic, making them suitable candidates for use as probiotics. These results are consistent with the findings of previous studies by Asadi et al (2022), Das et al (2022), andWei et al (2022), who identified various non-hemolytic Lactobacillus species isolated from different dietary foods and millet-based alcoholic drinks, and Wang et al (2018), who found no evidence of probiotic hemolytic activity in lactic acid bacteria from Chinese naturally fermented non-dairy food items. Many researchers (Asadi et al, 2022;Das et al, 2022;Wei et al, 2022;Chino de la Cruz et al, 2023) have reported similar findings, indicating that probiotics do not possess hemolytic activity, which reduce their safety for use as probiotics.…”
Section: Characterization and Screening Of Isolates For Probiotic Pro...supporting
confidence: 92%
See 2 more Smart Citations
“…In present study examining LAB strains for hemolytic activity, 16 strains were found to be non-hemolytic, making them suitable candidates for use as probiotics. These results are consistent with the findings of previous studies by Asadi et al (2022), Das et al (2022), andWei et al (2022), who identified various non-hemolytic Lactobacillus species isolated from different dietary foods and millet-based alcoholic drinks, and Wang et al (2018), who found no evidence of probiotic hemolytic activity in lactic acid bacteria from Chinese naturally fermented non-dairy food items. Many researchers (Asadi et al, 2022;Das et al, 2022;Wei et al, 2022;Chino de la Cruz et al, 2023) have reported similar findings, indicating that probiotics do not possess hemolytic activity, which reduce their safety for use as probiotics.…”
Section: Characterization and Screening Of Isolates For Probiotic Pro...supporting
confidence: 92%
“…Our study showed that, except BM2, all of the LAB strains tested grown at 37 • C after 24 h of incubation. The growth of LAB was limited at both 10 and 42 • C. Similar results were found in a previous investigation (Khusro et al, 2021;Wei et al, 2022;Amin et al, 2023), which supports these findings. In addition, all of our LAB isolates showed remarkable salt tolerance, even when exposed to 2% NaCl.…”
Section: Characterization and Screening Of Isolates For Probiotic Pro...supporting
confidence: 91%
See 1 more Smart Citation
“…This probiotic cntains a Cbp in its genome although the study did not attribute the probiotic property solely to the Cbp. 122 …”
Section: Adhesion Factors and Potential Downstream Mechanismsmentioning
confidence: 99%
“…Thammasorn et al ( Thammasorn et al, 2017 ) modified L. plantarum to produce hairpin RNA by transferring genes targeting YHV specific to this probiotic and were able to enhance resistance to YHV in shrimp consuming the probiotic while retaining the original function of the probiotic, which is to inhibit the development of some diseases. Another probiotic, W2, was found to be non-toxic, containing an active bacteriostatic component, and was able to antagonize seven strains of aquatic pathogens, while also promoting shrimp growth ( Wei et al, 2022 ). W2 appears to be equally useful for RNAi control in the same manner as L. plantarum .…”
Section: Preparation and Uptake Of Rnaimentioning
confidence: 99%